2020
DOI: 10.1038/s41586-020-2423-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of remdesivir in rhesus macaques infected with SARS-CoV-2

Abstract: Summary Effective therapeutics to treat COVID-19 are urgently needed. While many investigational, approved, and repurposed drugs have been suggested, preclinical data from animal models can guide the search for effective treatments by ruling out treatments without in vivo efficacy. Remdesivir (GS-5734) is a nucleotide analog prodrug with broad antiviral activity 1 , 2 , that is currently investigated in COVID-19 clinical tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
599
4
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 648 publications
(646 citation statements)
references
References 17 publications
25
599
4
18
Order By: Relevance
“… 10 Remdesivir has shown an in vitro activity on SARS-CoV-2 11 and a clinical benefit in rhesus macaques infected with SARS-CoV-2. 12 A large RCT has shown that remdesivir shortened the time to recovery in adults hospitalised with COVID-19 as compared with placebo but the results were not significant for mortality. 13…”
Section: Methods and Analysismentioning
confidence: 99%
“… 10 Remdesivir has shown an in vitro activity on SARS-CoV-2 11 and a clinical benefit in rhesus macaques infected with SARS-CoV-2. 12 A large RCT has shown that remdesivir shortened the time to recovery in adults hospitalised with COVID-19 as compared with placebo but the results were not significant for mortality. 13…”
Section: Methods and Analysismentioning
confidence: 99%
“…The current model suggests steric hindrance as a likely reason for termination, disturbing the positioning of the RNA and thus hampering the translocation to the next position 86 , 88 . RDV was shown to reduce virus replication of SARS-CoV-2 in vitro 90 and was demonstrated to restrict clinical symptoms of SARS-CoV-2 in rhesus macaques upon early pre-symptomatic treatment 91 . However, a recent randomized, double-blind, placebo-controlled clinical trial in humans with severe COVID-19 showed limited clinical efficacy of RDV treatment 92 and further studies will be necessary.…”
Section: Viral Gene Expression and Rna Synthesismentioning
confidence: 99%
“…Bao et al ( 111 ) and Chandrashekar et al ( 112 ) intratracheally and intranasally inoculated rhesus monkeys with the SARS-CoV-2 virus to study the possibility of reinfection. Williamson et al ( 113 ) used rhesus monkeys that had previously been inoculated through the intranasal, oral, ocular, and intratracheal routes for pharmacological research. These animals have also been used for the development of vaccines ( 106 , 107 , 114 , 115 ).…”
Section: In Vivo Models ( Table 2 )mentioning
confidence: 99%